An experimental-numerical method for estimating heat transfer in a Bridgman furnace - MOONEY, ROBIN; MCFADDEN, SHAUN (My University, 2014)
Direct measurement of heat flux and heat transfer coefficients in a Bridgman furnace is not always possible using traditional methods. This study characterised a vertical tubular Bridgman furnace using experimental data so that the estimated heat flux and heat transfer coefficients may be used in simulations of future experiments using the same furnace. An experimental–numerical method is presented where a discrete proportional integral derivative controller manipulates the radial heat flux in a front tracking solidification model so that the output temperature profile matches experimental data. The method is applicable for other experimentalists and modellers and its usefulness is demonstrated by example.
PUBLISHED
Keywords: Nanoscience & Materials; HEAT TRANSFER; Mechanical Engineering; SOLIDIFICATION